Ferritic stainless steel and its welding process and application
Patent Information
- Application Number
- CN202510514442.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]高温钎焊后的性能下降:现有的不锈钢材料在经过高温钎焊后,力学性能和耐腐蚀性均会出现显著下降
[0028]本发明提供的铁素体不锈钢,在高温环境下具有卓越的力学性能和耐腐蚀性能,在800℃时该铁素体不锈钢的抗拉强度>115MPa,屈服强度>80MPa,其屈服强度和抗拉强度在不同温度下均显著优于现有材料。该材料在耐腐蚀性能方面也有显著提升,在不锈钢三氯化铁点腐蚀试验中,腐蚀速率不超过77g/(m2·h),且穿孔时间>71min,可见该铁素体不锈钢在腐蚀性环境中具有更长的使用寿命。这种综合性能的提升,拓宽了该铁素体不锈钢的应用场景,促进了下游产业的发展。
Smart Images

Figure CN122959616A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of stainless steel materials technology, and in particular to a ferritic stainless steel and its welding process and applications. Background Technology
[0002] With the rapid development of new energy vehicles, especially hybrid vehicles, the automotive industry is placing increasingly higher demands on engine efficiency and exhaust emission control. To reduce fuel consumption and harmful emissions, an EGR (Exhaust Gas Recirculation) system is required on the engine side. The EGR cooler, a key component of this system, effectively lowers combustion temperature and reduces nitrogen oxide (NOx) formation by cooling high-temperature exhaust gases before recirculating them into the intake system. However, EGR coolers need to operate in high-temperature, high-pressure, and corrosive environments, posing numerous challenges to their design and material selection.
[0003] The core components of EGR coolers are typically made of ultra-pure ferritic stainless steel or austenitic stainless steel (such as 444, 443, 442, 441, 430LNT, 316L, etc.). These materials need to possess good wetting properties, gap-filling properties, and corrosion resistance after high-temperature brazing. Furthermore, the high-efficiency heat exchange unit of the cooler has a complex structure, with the thinnest part only 0.1mm, and the inlet air temperature may exceed 800℃, placing extremely high demands on the high-temperature resistance and corrosion resistance of the materials.
[0004] Although various high-performance stainless steel materials have been used in existing technologies, the following technical shortcomings still exist in practical applications:
[0005] Performance degradation after high-temperature brazing: Existing stainless steel materials exhibit a significant decrease in mechanical properties and corrosion resistance after high-temperature brazing. This makes EGR coolers prone to corrosion perforation during actual use, shortening their service life.
[0006] Insufficient corrosion resistance of materials: During operation, water vapor and sulfides in the exhaust gas of the EGR cooler may condense to form acidic condensate, which corrodes the internal materials of the cooler. Currently used stainless steel materials still have insufficient corrosion resistance, especially under the combined effects of high temperatures and acidic condensate.
[0007] The challenges of machining and brazing complex structures: EGR coolers typically contain a large number of stamped structures and complex fin structures. These structures are prone to deformation, oxidation, or uneven brazing seams during high-temperature brazing, which can affect the overall performance of the cooler.
[0008] Internal blockage and fatigue damage in the cooler: Due to the particulate matter in the exhaust gas, long-term use may lead to blockage of the internal passages of the cooler. In addition, the frequent switching between high and low temperatures in the cooler will cause thermal expansion and contraction, resulting in fatigue damage.
[0009] In view of this, the present invention is hereby proposed. Summary of the Invention
[0010] One of the objectives of this invention is to provide a ferritic stainless steel to solve at least one of the aforementioned technical problems.
[0011] The second objective of this invention is to provide a welding process for ferritic stainless steel.
[0012] The third objective of this invention is to provide an application of ferritic stainless steel.
[0013] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:
[0014] The first aspect of this invention provides a ferritic stainless steel with the following chemical composition: C≤0.025%, Si≤1.00%, Mn≤1.00%, P≤0.040%, S≤0.030%, Ni≤1.00%, 19.00%≤Cr≤24.00%, 1.50%≤Mo≤2.50%, N≤0.025%, and 1.00%≤W≤1.50%.
[0015] It also includes element M, which is Ti and / or Nb; the balance is Fe and unavoidable impurities.
[0016] In some embodiments of the present invention, the content of 8*(C+N)≤M in the ferritic stainless steel is ≤0.8%.
[0017] In some embodiments of the present invention, in the ferritic stainless steel, the element M is Ti and Nb.
[0018] In some embodiments of the present invention, Ti ≤ 0.15% in the ferritic stainless steel.
[0019] In some embodiments of the present invention, in the ferritic stainless steel...
[0020] 21.00 ≤ Cr ≤ 22.00%.
[0021] The second aspect of the present invention provides a brazing process for the aforementioned ferritic stainless steel, wherein the stainless steel workpiece is placed in a vacuum furnace, a vacuum is drawn, and the temperature is raised to the brazing temperature for brazing. After the brazing is completed, the workpiece is cooled to room temperature.
[0022] In some embodiments of the present invention, the heating rate is ≥10°C / min.
[0023] In some embodiments of the present invention, the brazing temperature is 1100–1110°C.
[0024] In some embodiments of the present invention, the brazing filler metal used in the brazing process includes nickel-based brazing filler metal.
[0025] In some embodiments of the present invention, the cooling rate is ≥20°C / min.
[0026] A third aspect of the present invention provides the application of the aforementioned ferritic stainless steel in the manufacture of EGR coolers.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects:
[0028] The ferritic stainless steel provided by this invention exhibits superior mechanical properties and corrosion resistance at high temperatures. At 800℃, its tensile strength >115MPa and yield strength >80MPa, significantly outperforming existing materials in both yield and tensile strength at different temperatures. This material also shows a significant improvement in corrosion resistance; in the ferric chloride pitting corrosion test, the corrosion rate does not exceed 77g / (m²). 2 The piercing time is greater than 71 minutes (·h), indicating that this ferritic stainless steel has a longer service life in corrosive environments. This improvement in overall performance broadens the application scenarios of this ferritic stainless steel and promotes the development of downstream industries.
[0029] The welding process provided by this invention is performed in a vacuum environment, effectively avoiding oxidation and impurity contamination, and ensuring the purity of the brazing process. By strictly controlling the heating rate, brazing temperature, and cooling rate, this process not only ensures the structural stability of stainless steel at high temperatures but also effectively inhibits grain growth and the formation of brittle phases, thus maintaining excellent mechanical properties and corrosion resistance after brazing. The cooling process further refines the grain structure, enhancing the material's fatigue resistance and creep resistance.
[0030] The application provided by this invention, given the advantages of the aforementioned ferritic stainless steel, enables it to effectively inhibit corrosion perforation under the high-temperature and corrosive conditions of EGR coolers, significantly improving the overall performance and reliability of the cooler, and providing an efficient and reliable solution for the automotive industry. Attached Figure Description
[0031] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0032] Figure 1 For example 1, the metallographic photograph of the prototype prepared in Example 1;
[0033] Figure 2 For example 1, a metallographic photograph of the prototype of comparative example 1;
[0034] Figure 3 The image shows the metallographic photograph of the welded joint obtained in Example 2. Detailed Implementation
[0035] The embodiments and examples of the present invention will be described in detail below with reference to the implementation methods and examples. However, those skilled in the art will understand that the following implementation methods and examples are only for illustrating the present invention and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0036] The first aspect of this invention provides a ferritic stainless steel with the following chemical composition: C≤0.025%, Si≤1.00%, Mn≤1.00%, P≤0.040%, S≤0.030%, Ni≤1.00%, 19.00%≤Cr≤24.00%, 1.50%≤Mo≤2.50%, N≤0.025%, and 1.00%≤W≤1.50%.
[0037] It also includes element M, which is Ti and / or Nb; the balance is Fe and unavoidable impurities.
[0038] The ferritic stainless steel provided by this invention exhibits superior mechanical properties and corrosion resistance at high temperatures. At 800℃, its tensile strength >115MPa and yield strength >80MPa, significantly outperforming existing materials in both yield and tensile strength at different temperatures. This material also shows a significant improvement in corrosion resistance; in the ferric chloride pitting corrosion test, the corrosion rate does not exceed 77g / (m²). 2 The piercing time is greater than 71 minutes (·h), indicating that this ferritic stainless steel has a longer service life in corrosive environments. This improvement in overall performance broadens the application scenarios of this ferritic stainless steel and promotes the development of downstream industries.
[0039] Element M is a stabilizing element for carbon (C), effectively improving the intergranular corrosion resistance of ferritic stainless steel. Ti and Nb form stable carbides (such as TiC and NbC) with carbon in stainless steel. These carbides form at grain boundaries, effectively fixing carbon atoms and preventing carbon segregation. Carbon segregation at grain boundaries leads to intergranular corrosion; therefore, the addition of Ti and Nb significantly improves the intergranular corrosion resistance of stainless steel. By stabilizing carbides, Ti and Nb effectively prevent the formation of chromium-depleted zones at grain boundaries, thereby improving the corrosion resistance of stainless steel in corrosive environments. Chromium-depleted zones are a major cause of intergranular corrosion in stainless steel; therefore, the addition of Ti and Nb is crucial for improving the corrosion resistance of stainless steel.
[0040] The addition of tungsten significantly improves the high-temperature mechanical properties, corrosion resistance, and overall performance of ferritic stainless steel, making it better suited for applications in high-temperature, high-pressure, and corrosive environments such as EGR coolers, providing crucial material support for the development of related industries. Chromium reacts with oxygen to form a dense chromium oxide film (passivation film) on the surface of stainless steel. This film effectively isolates the material from corrosive media, thereby improving its corrosion resistance. Within the range of 19.00% ≤ Cr ≤ 24.00%, increasing the chromium content significantly improves the stability and density of the passivation film, enhancing the material's corrosion resistance while maintaining good mechanical and processing properties.
[0041] Typical, but not limiting, chromium (Cr) content in ferritic stainless steel can be, for example, 19.00%, 20.00%, 21.00%, 22.00%, 23.00%, or 24.00%, or any value within the range of 19.00% to 24.00%; molybdenum (Mo) content can be, for example, 1.50%, 1.75%, 2.00%, 2.25%, or 2.50%, or 1.50%. The content of nitrogen (N) can be, for example, 0.010%, 0.015%, 0.020% or 0.025%, or any value in the range of 0.000% to 0.025%, but not exceeding 0.025%; the content of tungsten (W) can be, for example, 1.00%, 1.25%, 1.50% or 1.75%, or any value in the range of 1.00% to 1.50%.
[0042] In some embodiments of the present invention, the content of 8*(C+N)≤M in the ferritic stainless steel is ≤0.8%. Within this content range, sufficient stabilizing compounds can be formed at the grain boundaries, thereby effectively preventing intergranular corrosion. This ensures good mechanical and processing properties of the material while guaranteeing corrosion resistance.
[0043] In some embodiments of the present invention, in the ferritic stainless steel, the element M is Ti and Nb.
[0044] In some embodiments of the present invention, Ti ≤ 0.15% in the ferritic stainless steel.
[0045] In some embodiments of the present invention, in the ferritic stainless steel...
[0046] 21.00 ≤ Cr ≤ 22.00%.
[0047] Typical, but not limiting, chromium (Cr) content in ferritic stainless steel can be, for example, 21.00%, 21.10%, 21.20%, 21.30%, 21.40%, 21.50%, 21.60%, 21.70%, 21.80%, 21.90%, or 22.00%, or any value within the range of 21.00% to 22.00%.
[0048] The second aspect of the present invention provides a brazing process for the aforementioned ferritic stainless steel, wherein the stainless steel workpiece is placed in a vacuum furnace, a vacuum is drawn, and the temperature is raised to the brazing temperature for brazing. After the brazing is completed, the workpiece is cooled to room temperature.
[0049] The welding process provided by this invention is performed in a vacuum environment, effectively avoiding oxidation and impurity contamination, and ensuring the purity of the brazing process. By strictly controlling the heating rate, brazing temperature, and cooling rate, this process not only ensures the structural stability of stainless steel at high temperatures but also effectively inhibits grain growth and the formation of brittle phases, thus maintaining excellent mechanical properties and corrosion resistance after brazing. The cooling process further refines the grain structure, enhancing the material's fatigue resistance and creep resistance.
[0050] In some embodiments of the present invention, the heating rate is ≥10°C / min.
[0051] In some embodiments of the present invention, the brazing temperature is 1100–1110°C.
[0052] In some embodiments of the present invention, the brazing filler metal used in the brazing process includes nickel-based brazing filler metal. Using nickel-based brazing filler metal in the brazing process has excellent high-temperature performance, good wettability and gap-filling performance, good corrosion resistance, good compatibility with stainless steel, improved production efficiency and reduced costs, as well as environmental protection and safety.
[0053] In some embodiments of the present invention, the cooling rate is ≥20°C / min.
[0054] In one specific embodiment of the present invention, a stainless steel workpiece is placed in a vacuum furnace, and after vacuuming, it is heated to 1100-1110°C at a heating rate of ≥10°C / min for brazing. After brazing, it is cooled to room temperature at a cooling rate of ≥20°C / min. This process can effectively avoid oxidation and contamination, improve brazing quality, and optimize the microstructure of the material through rapid heating and rapid cooling, thereby improving its mechanical properties and corrosion resistance, and ensuring the reliability and service life of the workpiece in high temperature, high pressure and corrosive environments.
[0055] A third aspect of the present invention provides the application of the aforementioned ferritic stainless steel in the manufacture of EGR coolers.
[0056] The application provided by this invention, given the advantages of the aforementioned ferritic stainless steel, enables it to effectively inhibit corrosion perforation under the high-temperature and corrosive conditions of EGR coolers, significantly improving the overall performance and reliability of the cooler, and providing an efficient and reliable solution for the automotive industry.
[0057] The present invention is further illustrated below with specific embodiments and comparative examples. However, it should be understood that these embodiments are merely for illustrative purposes and should not be construed as limiting the invention in any way. Unless otherwise specified, the raw materials used in the embodiments and comparative examples of the present invention were carried out under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0058] Examples and Comparative Examples
[0059] The content of each component in the raw materials of the ferritic stainless steels of the examples and comparative examples is shown in Table 1 below.
[0060] Table 1
[0061]
[0062] Test Example 1
[0063] The tensile strength and yield strength of the ferritic stainless steels obtained in the examples and comparative examples were tested, and the data are shown in Table 2 below.
[0064] The tensile strength and yield strength tests were conducted in accordance with the provisions of GB / T 228.2-2015 Metallic materials, tensile testing - Part 2: High temperature test methods.
[0065] Table 2
[0066]
[0067]
[0068] As shown in Table 2, increasing the W and Mo content in stainless steel can significantly improve its high-temperature strength. In Example 1, by adding W, the high-temperature tensile strength and yield strength were increased by more than 20% compared to Comparative Examples 3 and 4.
[0069] Test Example 2
[0070] The ferritic stainless steels obtained in the examples and comparative examples were subjected to corrosion resistance tests. The corrosion resistance test process was carried out in accordance with the provisions of GB / T 17897-2016, and the data obtained are shown in Table 3 below.
[0071] Table 3
[0072]
[0073] The corrosion resistance coefficient can be defined as Cr% + 3(Mo% + W%). As can be seen from Table 3, the larger the corrosion resistance coefficient of stainless steel, the longer the perforation time of the test specimen and the smaller the corrosion rate, that is, the better the corrosion resistance of stainless steel.
[0074] Test Example 3
[0075] The ferritic stainless steel obtained in Example 1 was brazed under different process conditions, with four different processes set up:
[0076] Process 1: The heating rate is set to 8℃ / min, the cooling rate to 15℃ / min, and the brazing temperature to 1150℃.
[0077] Process 2: The heating rate is set to 10℃ / min, the cooling rate to 20℃ / min, and the brazing temperature to 1150℃.
[0078] Process 3: Set the heating rate to 10℃ / min, the cooling rate to 20℃ / min, and the brazing temperature to 1100℃.
[0079] Process 4: Set the heating rate to 12℃ / min, the cooling rate to 25℃ / min, and the brazing temperature to 1100℃.
[0080] After completing the brazing processes described above, the corrosion resistance of each sample was tested according to GB / T 4334.6-2015 Stainless Steel 5% Sulfuric Acid Corrosion Test Method. The data obtained are shown in Table 4 below.
[0081] Table 4
[0082]
[0083] As can be seen from Table 4, increasing the brazing heating rate and cooling rate, and decreasing the brazing temperature can effectively improve the corrosion resistance of the material.
[0084] Example 1
[0085] The ferritic stainless steels obtained in Example 1 and Comparative Example 1 were stamped, assembled, and brazed to obtain prototype parts. During the welding process, it was found that the stainless steel in Comparative Example 1 oxidized during brazing, the brazing filler metal could not wet and fill the gap, and the welding quality could not meet the requirements.
[0086] Metallographic photographs were taken of the obtained prototypes, and the metallographic photographs correspond to the following: Figure 1 and Figure 2 As shown.
[0087] from Figure 1 As can be seen, the weld seam of the prototype is full, with good microstructure and morphology, and no obvious defects or abnormalities are observed.
[0088] from Figure 2 As can be seen, solder accumulates in the area where it was applied, the weld is not completely filled, and the welding quality does not meet the requirements.
[0089] Example 2
[0090] Metallographic images were taken of the welded joints of the ferritic stainless steels obtained in Example 1 and Comparative Example 2 after welding. The metallographic images are as follows: Figure 3 As shown.
[0091] from Figure 3 As can be seen, the metallographic structure of Example 1 is normal. In Comparative Example 2, a hard and brittle diffusion layer with a thickness of about 100 μm appears near the weld. This layer is prone to brittle fracture during product use and also reduces the corrosion resistance of the material.
[0092] Compared to Example 1, Comparative Example 2 has a higher Cr content and thus better corrosion resistance. However, due to its excessively high Cr content, a large number of hard and brittle phases were generated at the contact point between Comparative Example 2 and the weld during the brazing process, which adversely affected the performance of the stainless steel.
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical embodiments of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical embodiments described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical embodiments to deviate from the scope of the technical embodiments of the present invention.
Claims
1. A ferritic stainless steel, characterized in that, The chemical composition includes: C≤0.025%, Si≤1.00%, Mn≤1.00%, P≤0.040%, S≤0.030%, Ni≤1.00%, 19.00%≤Cr≤24.00%, 1.50%≤Mo≤2.50%, N≤0.025%, and 1.00%≤W≤1.50%. It also includes element M, which is Ti and / or Nb; the balance is Fe and unavoidable impurities.
2. The ferritic stainless steel according to claim 1, characterized in that, 8*(C+N)≤M content≤0.8%.
3. The ferritic stainless steel according to claim 1, characterized in that, The element M is Ti and Nb.
4. The ferritic stainless steel according to claim 3, characterized in that, Ti≤0.15%.
5. The ferritic stainless steel according to claim 1, characterized in that, 21.00≤Cr≤22.00%。 6. A brazing process for ferritic stainless steel according to any one of claims 1 to 5, characterized in that, The stainless steel workpiece is placed in a vacuum furnace, and after vacuuming, it is heated to the brazing temperature for brazing. After brazing, it is cooled to room temperature.
7. The brazing process according to claim 6, characterized in that, The heating rate is ≥10℃ / min.
8. The brazing process according to claim 6, characterized in that, The brazing temperature is 1100~1110℃; Preferably, the brazing filler metal used in the brazing process includes nickel-based brazing filler metal.
9. The brazing process according to claim 6, characterized in that, The cooling rate is ≥20℃ / min.
10. The use of a ferritic stainless steel according to any one of claims 1 to 5 in the manufacture of an EGR cooler.